PERAN GURU DALAM MENGEMBANGKAN KETERAMPILAN MENULIS DESKRIPSI PADA SISWA SEKOLAH DASAR - Rahmawati, Siti (Universitas Sulawesi Tenggara, 2023)
This study discusses the role of teachers in developing descriptive writing skills in elementary school students. Descriptive writing skills are important skills that need to be developed early on, because these skills are the foundation for more complex language and critical thinking skills. The role of teachers is very important in guiding students to be able to observe, understand, and express ideas descriptively through words. Through targeted learning strategies, such as the use of visual media, observation exercises, writing examples, the five-sensory approach, and constructive feedback, teachers can help students understand and apply descriptive writing techniques well. In addition, collaboration between students and the provision of a variety of descriptive vocabulary also enrich students' writing skills. The results of the study show that the active role of teachers and the right strategies can improve elementary school students' descriptive writing skills, so that they are more skilled in observing, thinking critically, and expressing themselves.